Min al-Ḥall ilā al-Qawmiyyah: Fiqh as-Siyāsah li al-Qam‘i al-Jadalī Tijāh al-Jamā‘āt al-Islāmiyyah bi Indūnīsiyā - Wibowo, Waskito; Yasin , Yuli; Mohammad Syairozi Dimyathi; Anwar, Saepul (Faculty of Sharia IAIN Madura collaboration with The Islamic Law Researcher Association (APHI), 2025)
During his second term, President Joko Widodo took decisive action by dissolving two prominent Islamist organizations in Indonesia, Hizbut Tahrir Indonesia (HTI) and the Islamic Defenders Front (FPI). This study explores how the Indonesian government has sought to strengthen its position and gain the trust of nationalist and moderate Islamic factions through anti-Islamist policies. By utilizing Islam as a political tool, the administration has fostered nationalism while suppressing Islamist and conservative movements. Employing a case study and fiqh siyasah conceptual approach and analyzing secondary data from books, journals, and media, this research examines three key questions: how Indonesian presidents have historically interpreted Islamism, how identity has been used to fuel animosity between Islamists and Jokowi’s administration, and the impact of dissolving Islamic organizations on Indonesia's democratic future. The findings reveal that religion has been exploited for political purposes, posing a threat to freedom of expression and assembly in a democracy, while Jokowi’s administration has strategically used Islamism to consolidate its power and public trust. This matter, in fact, gains legitimacy from the political jurisprudence that the Islamic group seeks to promote.